Ultra-sensitive and highly selective H2 sensors based on FSP-made Rh-substituted SnO2 sensing films - Inyawilert K. (2017)
© 2016 Elsevier B.V. In this research, SnO 2 nanoparticles doped with 0.1–2 wt% rhodium (Rh) were synthesized by flame spray pyrolysis and systematically investigated for H 2 -sensing applications. From X-ray and electron microscopic characterizations, SnO 2 nanostructures exhibited spheroidal morphology with polycrystalline tetragonal SnO 2 phase and Rh might form solid solution with SnO 2 lattice. The sensing films were prepared by spin coating technique and their gas-sensing performances were studied at the operating temperatures ranging from 100 to 350 °C in dry air. Gas-sensing measurements showed that SnO 2 sensing films with the optimal Rh-doping level of 0.2 wt% exhibited an ultra-high response of ∼22,170, which was more than three orders of magnitude higher than that of undoped one, and a short response time of 6 s towards 30,000 ppm H 2 at an optimum operating temperature of 300 °C. In addition, the optimal Rh-doped SnO 2 sensor displayed high H 2 selectivity against NO 2 , SO 2 , C 2 H 4 , C 3 H 6 O, CH 4 , H 2 S and CO. Thus, Rh-doped SnO 2 nanoparticulate thick films are promising candidates for H 2 -sensing applications.